2019
DOI: 10.1016/j.ijid.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of Crimean-Congo Hemorrhagic Fever (CCHF) in Afghanistan: Reported cases to National Surveillance System, 2016–2018

Abstract: This study aims to provide descriptive epidemiology of human CCHF cases in Afghanistan by demographic, geographical, and seasonal characteristics. Methodology: This paper's findings are based on the retrospective analysis of the National Surveillance System's collected data from 2016 to 2018. Weekly cases exceeding the 90th percentile of the expected number of cases were considered to be exceptional and above normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 10 publications
(16 reference statements)
4
25
0
Order By: Relevance
“…Previous investigation of CCHF patients admitted in a tertiary care hospital in Karachi showed most cases were students and butchers [25]. Data from a CCHF endemic and neighboring country Afghanistan revealed housewives, health staff, shepherds and butchers to be the high risk occupational groups [26]. Notably, in the present study no case of CCHF was observed in healthcare personnel suggesting good awareness about the disease and strict implementation of infection prevention and control in such settings.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 41%
“…Previous investigation of CCHF patients admitted in a tertiary care hospital in Karachi showed most cases were students and butchers [25]. Data from a CCHF endemic and neighboring country Afghanistan revealed housewives, health staff, shepherds and butchers to be the high risk occupational groups [26]. Notably, in the present study no case of CCHF was observed in healthcare personnel suggesting good awareness about the disease and strict implementation of infection prevention and control in such settings.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 41%
“…In this study the most affected age group was 20-29 years which is the economically active age. The similar observation were noted in descriptive study done in Afghansitan (Sahak et al, 2019). Previous studies have reported the most affected age group is 13-45 years, which is comparable to our study (Mofleh & Ahmad, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Also in a recent study, CCHFV genomes in sheep, and CCHFV‐specific antibodies in sheep and goats were found in these areas (Kasi et al, ). This region is close to the border with Afghanistan, which is also endemic for CCHFV (Khurshid et al, ; Sahak, Arifi, & Saeedzai, ). Balochistan is considered as a corridor for the trade of ruminant skins from Iran (also endemic for CCHFV) and Afghanistan for the leather industry, and also importation of livestock from Afghanistan to Pakistan is common (Raziq, Younas, & Rehman, ).…”
Section: Discussionmentioning
confidence: 99%